Efficacy of topical steroids in preventing radiation dermatitis: A systematic review and meta‐analysis - Shao, Xinyi; Chen, Tingqiao; Li, Hao; Chen, Yangmei; Zhang, Yujie; Chen, Jiayi; Li, Yuxin; Liu, Lin; Pu, Yihuan; Chen, Jin (Dermatologic therapy, 2022)
To evaluate the relative efficacy of topical steroids in preventing radiation dermatitis (RD). Multiple databases including Medline, Cochrane Library, Embase, Web of Science, China National Knowledge Infrastructure (CNKI), China Biological Medicine (SinoMed), and Wanfang Database were searched for randomized controlled trials (RCTs) of RD prevention in patients with cancer from inception to November 26, 2021, followed by an update on June 1, 2021. Six RCTs evaluating the efficacy of topical steroids in preventing RD in a total of 661 patients with cancer were included. RD incidence was lower with topical steroids compared with placebo at week 3 (relative risk [RR] = 0.68, 95% confidence interval [CI]: 0.31–1.50) and at radiation therapy (RT) completion (RR = 0.97, 95% CI: 0.93–1.00). Topical steroids demonstrated a less risk of developing dermatitis of Radiation Therapy Oncology Group (RTOG) grades 2 and 3 at the completion of RT (RR = 0.66, 95% CI: 0.55–0.80 and RR = 0.54, 95% CI: 0.38–0.77, respectively). However, topical steroids did not reduce RTOG grades 1 and 2 dermatitis at week 3(RR = 0.73, 95% CI: 0.45–1.14 and RR = 0.66, 95% CI: 0.27–1.60, respectively). Notably, the use of topical steroids did not decrease RD incidence when patients received combined chemotherapy (RR = 0.60, 95% CI: 0.42–0.86), and an obvious reduction in the incidence of RD at RT completion was found when patients used the topical steroids twice‐daily (RR = 0.66, 95% CI: 0.47–0.93, P = 0.02). Topical steroids reduced RD incidence in patients receiving RT. Thus, twice‐daily topical steroids may be recommended for patients at the beginning of RT.